2019
DOI: 10.1136/bmjopen-2019-031434
|View full text |Cite
|
Sign up to set email alerts
|

The Upper Gastrointestinal Cancer Registry (UGICR): a clinical quality registry to monitor and improve care in upper gastrointestinal cancers

Abstract: PurposeThe Upper Gastrointestinal Cancer Registry (UGICR) was developed to monitor and improve the quality of care provided to patients with upper gastrointestinal cancers in Australia.ParticipantsIt supports four cancer modules: pancreatic, oesophagogastric, biliary and primary liver cancer. The pancreatic cancer (PC) module was the first module to be implemented, with others being established in a staged approach. Individuals are recruited to the registry if they are aged 18 years or older, have received car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…A stratified purposeful sampling strategy was used to recruit participants, followed by snowball sampling [ 21 ]. This initially involved inviting by email clinicians contributing to the UGICR and clinicians identified as specialising in PC on hospital websites [ 15 ]. In addition, those interviewed were asked to nominate other specialists for researchers to contact.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A stratified purposeful sampling strategy was used to recruit participants, followed by snowball sampling [ 21 ]. This initially involved inviting by email clinicians contributing to the UGICR and clinicians identified as specialising in PC on hospital websites [ 15 ]. In addition, those interviewed were asked to nominate other specialists for researchers to contact.…”
Section: Methodsmentioning
confidence: 99%
“…A set of quality indicators for PC was developed by Australian clinicians in 2018 and compliance with these indicators is reported by the Upper Gastrointestinal Cancer Registry (UGICR) [ 14 , 15 ]. Preliminary analysis of registry data found that 29% (n = 64/224) of patients with potentially resectable and 43% (n = 54/125) of patients with locally advanced disease (without metastases) did not undergo either a documented PPCT or MRI.…”
Section: Introductionmentioning
confidence: 99%
“…Interested participants could either contact the researcher via telephone, email or the prepaid envelope to express an interest in participating. The UGICR is a clinical quality registry that collects information pertaining to the diagnosis, treatment and outcomes of patients with upper gastrointestinal cancers, and has coverage of approximately 70% of pancreatic cancer cases and 55% of OG cancer cases diagnosed across Victoria [12]. Purposeful sampling was used to recruit participants from a range of socio-demographic backgrounds.…”
Section: Recruitment and Consentmentioning
confidence: 99%
“…The 5-year survival rate for oesophagogastric and pancreaticobiliary cancers is amongst the worst of all tumour types [ 1 ]. Surgical resection, which is the primary curative treatment, can suppress immune function and increase the risk of infection.…”
Section: Introductionmentioning
confidence: 99%